2017
DOI: 10.1212/wnl.0000000000003740
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of beneficial effects of plasmapheresis in natalizumab-associated PML

Abstract: This study provides Class III evidence that for patients with NTZ-PML, PLEX does not improve survival. The study lacks the statistical precision to exclude an important benefit or harm of PLEX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…In addition, plasma exchange has been shown to be ineffective in natalizumab-associated PML cases. 8 Faced with progressive clinical deterioration and rising JCV-DNA in the CSF despite steroids, it was decided to start G-CSF, a glycoprotein, which primarily stimulates the production, mobilization, and survival of neutrophils, to initiate immune reconstitution in December 2016. Stefoski highlighted the clinical benefit of G-CSF in PML in 8/16 patients, with the desired response of immune-boosting leukocytosis and lymphocytosis resulting in IRIS in 16/18 patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, plasma exchange has been shown to be ineffective in natalizumab-associated PML cases. 8 Faced with progressive clinical deterioration and rising JCV-DNA in the CSF despite steroids, it was decided to start G-CSF, a glycoprotein, which primarily stimulates the production, mobilization, and survival of neutrophils, to initiate immune reconstitution in December 2016. Stefoski highlighted the clinical benefit of G-CSF in PML in 8/16 patients, with the desired response of immune-boosting leukocytosis and lymphocytosis resulting in IRIS in 16/18 patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to these findings, they suggested that the spontaneous recovery of immunocompetence after natalizumab withdrawal might counteract the spread of PML and therefore not require any additional intervention. 9 In a case report, plasmapheresis was not performed due to lesion being asymptomatic and of a small size. The consequent IRIS was quite limited in time and space.…”
Section: Discussionmentioning
confidence: 99%
“…There are small case series showing the efficacy of maroviroc (a CCR5 antagonist) for the treatment of PML-IRIS 58,59. A more detailed discussion regarding the approach to treatment of natalizumab-associated PML is beyond the scope of this review but is available elsewhere 54,57,60,61…”
Section: Natalizumab Safety and Tolerabilitymentioning
confidence: 99%